Students' perspective on incorporating Arabic words in the teaching of English to Muslim learners - Othman, Khairiah; Mohammad Lotfie, Maskanah (Arab World English Journal (AWEJ), 2013)
The presence of words and concepts in the English language that do not correspond with the meaning held by Muslims has been highlighted by many Muslim scholars. It is argued that there are many English words fail to reflect the meanings that Muslims intend to convey due to the fact that many Arabic words are not accurately translatable into English. Furthermore, Muslims believe that many of the meanings of Arabic words and phrases are of divine provenance and may not be separated from their Arabic forms. Based on al-Faruqi’s framework on Islamic English that proposes the use of Islamic vocabulary be retained in their Arabic form in an effort to maintain the original meanings, this study investigated postgraduate Muslim students’ perspective on whether there is a need for Islamic Arabic vocabulary to be incorporated in the teaching of English to Muslim learners. A survey consisting of open-ended questions was administered and the findings indicate that the respondents strongly favoured the incorporation of Islamic terms in English language teaching. This paper has pedagogical implications on ESL teachers who teach English to Muslim learners. Keywords: vocabulary learning, Muslim English language learners, Islamic English